STUDI KUALITAS AIR IRIGASI DUMOGA DI KABUPATEN BOLAANG MONGONDOW PROVINSI SULAWESI UTARA - Wantasen, Sofia; Luntungan, Joudie. N. (Bumi Lestari, 2017)
Water Irrigation a very important and is one key to the success of the increased production of rice plants in the paddy field.  The aim of this study was to assess the water quality Irrigation Dumoga at Kabupaten Bolaang Mongondow Province Sulawesi Utara. Data collected by observation of agriculture activity and determination of sampling by using composite sampling method at canal Irrigation Dumoga. Measurement in situ pH, and temperatur.  Analysis concentration total dissolved solid (TDS), total suspended solid (TSS), conductivity (DHL), nitrate and phosphate, sodium, calcium, magnesium in the Laboratory.  Method data analysis are Graphic Method and to compare with standart Goverment PP. No. 82/2001 Class IV, and Sodium Absorption Ratio (SAR) Analysis.    The results showed that temperatur at canal Irrigation Motabang 29,3 C, pH 7,12, value of the total dissolved solid (TDS) 127 mg/l, total suspended solid (TSS) 7 mg/l, conductivity (DHL) 182 µS/cm, nitrate 0,040 mg/l, phosphate 0,076 mg/l  mg/l eligible accordance with the standard PP No. 82/2001 Kelas IV.  Natrium concentration 6,38 mg/l, kalsium 0,76 mg/l, magnesium 0,27 mg/l.